Development of Socio-Scientific Issues-Based Worksheets to Increase Learning Interest and Critical Thinking Skills of Students on Buffer Solution Material - Sirmayeni, Sirmayeni; Rery, Radjawali Usman; Anwar, Lenny (Journal of Natural Science and Integration, 2024)
This study is intended to develop a worksheet based on socio-scientific issues for buffer solution material that is valid and reliable in order to determine the increase in students' learning interest and critical thinking skills. The Research and Development (R&D) method with the ADDIE model was employed, encompassing five phases: analysis, design, development, implementation, and evaluation. Data collection techniques included interviews, student questionnaires, validation sheets, and user response questionnaires. Two methods were used in small-scale trials: one-on-one tests and user response assessments. The one-on-one test involved three students with high, medium, and low abilities. The user response assessment involved three teachers and 30 students from SMAN 4 Pekanbaru, SMAN 8 Pekanbaru, and SMAN 15 Pekanbaru. The difference in the effect of using the worksheet on improving critical thinking skills and learning interest was analyzed using the t-test. To determine whether there was an increase in critical thinking skills, as indicated by improved student grades, the N-Gain formula was applied. The results showed that the developed worksheet obtained average percentages of 92% from material experts and 98% from media experts, indicating valid criteria. The one-on-one test provided students' comments on necessary improvements to the worksheet components. User responses from teachers and students resulted in 93.1% and 93.7% respectively, indicating that good criteria were achieved. The paired t-test on learning interest data showed a significance value of 0.000 (sig < 0.05), indicating a significant difference in students' learning interest before and after using the worksheet. Similarly, the critical thinking skills data showed a significance value of 0.000 (sig < 0.05), indicating a significant difference in students' critical thinking skills before and after using the worksheet. Based on the posttest results of the experimental and control classes, it was found that the student worksheets improved students' critical thinking skills to a medium level, with an N-Gain value of 53.93. In contrast, the control class showed a low improvement, with an N-Gain value of 30.00.Keywords: worksheet, Socio-Scientific Issues, interest in learning, critical thinking skills, buffer solution